PRESCRIPTION AND ADEQUACY OF HEMODIALYSIS IN DEPARTMENT OF NEPHROLOGY AND DIALYSIS GI "INSTITUTE OF NEPHROLOGY OF NAMS OF UKRAINE" FOR 2012 YEAR. - M. V. Kulyzkyi; J. S. Busygina; N. V. Stashevska; A. V. Bilenko; l. M. Surgko (Ukrainian Journal of Nephrology and Dialysis, 2017)
Work of department of HD of GI "Institute of nephrology of NAMSU" is analyzed and compared to mean for Ukraine and some regions according National register of patients with chronic kidney diseases 2011.